A 3D‐Printed Self‐Learning Three‐Linked‐Sphere Robot for Autonomous Confined‐Space Navigation. (21st September 2021) - Elder, Brian; Zou, Zonghao; Ghosh, Samannoy; Silverberg, Oliver; Greenwood, Taylor E.; Demir, Ebru; Su, Vivian Song-En; Pak, On Shun; Kong, Yong Lin
Abstract : Robots In article number 2100039, Yong Lin Kong and co‐workers present a 3D‐printed, compact robot integrated with reinforcement learning that performs adaptable, autonomous crawling in a confined environment. Without prior knowledge of the environment, the scalable robot can learn effective locomotory gaits that enable navigation through confined and dynamic environments, addressing a key challenge for robotic biomedical diagnosis.